Novel endoscopic terminology: NBI visualization - Vadim Dmitrievich Kreymer; Vladimir Petrovich Tyurin; Evgeniya Aleksandrovna Kogan; V D Kreimer; V P Tyurin; E A Kogan (Терапевтический архив, 2011)
Aim. To develop new criteria of gastric and duodenal mucosa image assessment using endoscopic system for narrow band imaging (NBI). Material and methods. Endoscopic and morphological findings were compared in 460 patients with different chronic diseases of the stomach and duodenum. Esophagogastroduodenoscopy was made according to the standard technique by the gastroduodenoscope EVIS EXERA-II GIF H180 (Olympus, Japan) with NBI-system. Biopsy material was studied by standard pathomorphological techniques. Results. The novel system of the visual picture evaluation during conduction of endoscopic investigations in monochromatic light provides higher significance of identification of inflammatory and destructive processes in mucosa including foci of structural alterations, their location and extent. Conclusion. We propose a protocol for description of the endoscopic picture in conduction of examinations with application of the NBI-system of visualization in monochromatic light. It can help physicians to correctly estimate the image and interpret the detected changes.